ANALISIS PENDAPATAN DAN EFISIENSI PRODUKSI PADI ORGANIK PADA KELOMPOK TANI NGUDI RAHARJO DI DUSUN BENYO KELURAHAN SENDANGSARI KEPANEWON PAJANGAN - Chrisma Agustina; Anggraeni, Rini; Cungki Kusdardjito (Fakultas Pertanian Universitas Janabadra, 2025)
This study was conducted with the aim of analyzing the income and efficiency of organic rice production at the Ngudi Raharjo Farmer Group in Benyo Hamlet, Sendangsari Village, Pajangan District with a sample of 30 farmers. Hypothesis testing used the methods (1) income analysis (2) Coob-Douglass function analysis using the Data Envelopment Analysis (DEA) program. The results showed that the average income from organic rice farming was IDR 16,969,582/farm. The total cost of expenditure was IDR 3,193,584/farm. The income received was greater than the total cost of expenditure. The profit was IDR 16,718,082/farm. Organic rice farming is feasible because the R/C ratio value of 6.31 is greater than 1. The economic efficiency value for input of growth stimulants is 3.64; botanical pesticides 0.201. Technically, the use of production inputs of 1.086 > 1 has an Increasing Return to Scale.